Transport and sustainable development - Mpe, Raisibe Gwendoline (Univerzita Pardubice, 2012)
The aim of this thesis is to align the role of transportation together with sustainable development to achieve sustainable transportation. Sustainable transportation aims to provide better and healthier ways of meeting individual and community needs while reducing the environment and social impacts of current mobility practise. Negative impacts on environment, economic growth and social equity have led to governments and other organisations to come up with policies and strategies to improve current unsustainable situation such as: traffic congestion, air pollution, climate change, transport cost, accessibility etc.. Transportation is a non-separable part of society, which is why working toward a sustainable future in transportation should be a responsibility of everyone.
Doprava a udržitelný rozvoj
Keywords: udržitelný rozvoj; doprava; změna klimatu; sociální spravedlnost a mobilita; sustainability; trasportation; climate changes; social equity and mobility